Application of Balankin Fractal Model to the Fractal Volcanic Activity Model - Brenes-André, José (2014)
The Sequential Fragmentation Theory (SFT, Brown, 1989) is based on sequential fragmentation at macroscopic level. Fractal model proposed by Brenes & Alvarado (2013), with the help of Hurst coefficient H, includes vesicle coalescence and their degassing, thus systematizing the whole process. In this work Balankin fractal fracture model is added. Volcanic fragmentation process is then explained from the micro to the macro level. The existence of two universal fracture values, already experimentally found, is predicted.